Diagnostic work-up and phenotypic characteristics of a family with variable severity of distal arthrogryposis type 2B (Sheldon-Hall syndrome) and TNNT3 pathogenic variant - Dabaj, Ivana; Carlier, Robert Y.; Dieterich, Klaus; Desguerre, Isabelle; Faure, Julien; Romero, Norma B.; Trang, Wenting; Quijano-Roy, Susana; Germain, Dominique P. (Frontiers in Genetics, 2023)
Background: Distal arthrogryposis (DA) is a group of rare, clinically, and genetically heterogeneous disorders primarily characterized by congenital contractures of the limb joints. Sheldon-Hall syndrome (SHS; OMIM #601680 or DA2B) is a rare multiple congenital contracture syndrome characterized by contractures of the distal joints of the limbs and mild facial involvement. SHS is intermediate to DA1 and DA2A (also known as Freeman-Sheldon syndrome, FSS; OMIM#193700) and was found to be due to pathogenic variants in genes encoding the fast-twitch skeletal muscle contractile myofibers complex. Patients and methods: A 16-year-old boy with a history of congenital distal arthrogryposis presented to our multidisciplinary consultation with severe kyphoscoliosis and respiratory insufficiency. Both his mother and younger sister, who had not previously searched for medical attention, were found to have phenotype compatible with SHS although to a lesser extent. Diagnostic work up included complete physical exam, Eos, whole body muscular MRI (WBMRI) in all three patients, together with ENMG studies and muscle biopsy in the index case. DNA sequencing was used to confirm the clinical diagnosis. Results: Detailed physical examination suggested the clinical diagnosis of SHS. No major signal abnormalities were found in WBMRI for all three individuals. Neurogenic changes were observed on needle EMG and on the muscle biopsy in the index patient. DNA sequencing revealed a missense mutation in TNNT3 (c.187C>T; p.Arg63Cys). This mutation was confirmed to segregate with the SHS phenotype in affected individuals in the family. Discussion: This is the first report of neurogenic involvement in a patient with DA2B. A missense mutation was identified at codon 63 of the TNNT3 gene, a mutational hotspot. Although TNNT3 encodes the fast-twitch skeletal muscle contractile myofibers complex, our data suggests (additional) chronic nerve injury underlying this arthrogryposis syndrome. Keywords: Sheldon-Hall syndrome, distal arthrogryposis type 2B (DA2B), TNNT3, neurogenic pattern, distal contractures, kyphoscoliosis. Abbreviations: DA: Distal arthrogryposis, EMG: Electromyography, EOS: FSS: Freeman-Sheldon syndrome, SHS: Sheldon-Hall Syndrome or DA2B, TNN: troponin, TPM2: tropomyosine 2, MYH3: embryonic myosin heavy chain 3, MYBPC1: myosin binding protein C1.